The Power Consumption Performance of an Orbiting Screw Solid-Solid Mixer - Semuel Pati Senda; Renanto Renanto; Achmad Roesyadi; Wahono Sumaryono; Yazid Bindar (Institute for Research and Community Services, Institut Teknologi Bandung, 2012)
In this work we have investigated mixing in a modified orbiting screw mixer (MOSM) designed for solid-solid mixing. Mixing was carried out using urea powder and natural zeolite powder (UZ) of three varying particle sizes (50-60, 60-80 and 80 mesh). Power consumption was calculated from the measured torque of orbit and screw, obtained from computerized records. It was found that the mixing process in the modified orbiting screw mixer with air injection required a lower power consumption for each particle-size group when compared to mixing without air injection. With UZ mixing in MOSM with air injection, the lowest E was obtained for the 60-80 mesh particle-size group (4,297 Joule/kg-1),whereas when mixing without air injection, the value was 10,296 J/kg. The best mixing operation in this experiment was achieved at NFr = 1.18x10-3 and in the range of values NReâ‰ˆ 8.77x107 to 2.63x108. Moreover, in this study, we have developed an equation to estimate the power consumption required for mixing and determined its correlation with dimensionless numbers.